Scope of CSR in Islamic Economics and Finance - Abdalrahman Mohamad Migdad (Islamic Economics Journal, 2021)
The purpose of this paper is to explain the scope of Corporate Social Responsibility (CSR) and the Islamic understanding of what responsibility means. The paper aims to reflect on the originality of the idea in the Islamic economic tradition and analyze CSR factors special to Islamic economic institutions. An extensive analysis of existing literature is undertaken to present findings that support the idea of CSR being original in Islamic economics. Within this wide scholarly debate and research on CSR, the views of essential scholars are presented. Finally, an analysis of different drivers for a corporation's engagement in CSR is presented alongside some drivers unique to Islamic financial institutions. Findings: CSR as a research idea is an ongoing debate, especially concerning the definition and operation margins. However, this is a healthy sign showcasing flexibility facing changing community and social needs and the corporation's capabilities and interests. Furthermore, indirect CSR, such as fighting corruption and sensitivity to sharia-compliant operations, needs to be addressed more in light of CSR. The paper finds that the lack of anti-corruption measures and sharia compliance is socially irresponsible and may cost more than corporations might spend directly under CSR. The value of this research is that it shows a need for more CSR engagement from corporations as well as better understanding from the engaged public on the goals and limits of different corporations; one that stands out is Islamic banks and what people expect.